Tolterodine Extended Release Is Efficacious in Continent and Incontinent Subjects with Overactive Bladder - Rovner, Eric S.; Rackley, Raymond; Nitti, Victor W.; Wang, Joseph T.; Guan, Zhonghong (Urology (Ridgewood, N.J.), 2008)
To assess efficacy and tolerability of tolterodine extended release (ER) in continent and incontinent subjects with overactive bladder (OAB). This was a post hoc analysis of data from a 12-week, double-blind, placebo-controlled trial of tolterodine ER (4 mg once daily). Subjects completed 7-day bladder diaries at baseline and week 12; those with one or more incontinence episode(s) in their diaries at baseline were considered incontinent. Subjects rated urgency associated with each micturition on a scale from 1 to 5, and micturitions were categorized post hoc by urgency rating as non-OAB (1-2), OAB (3-5), or severe OAB (4-5). At baseline, 40% of subjects were incontinent. Tolterodine ER (n = 429) reduced total, OAB, and severe OAB micturitions compared with placebo (n = 421) in continent and incontinent subjects. There was no difference between continent and incontinent subjects in terms of the magnitude of improvement with tolterodine ER relative to placebo for total, OAB, and severe OAB micturitions. Reductions in mean urgency and frequency-urgency sum ratings were significantly greater in the tolterodine ER group. Among incontinent subjects, tolterodine ER significantly reduced urgency urinary incontinence episodes and significantly increased the percentage of subjects achieving continence relative to placebo. Adverse event rates were low in both continent and incontinent subjects. Tolterodine ER reduced micturitions associated with urgency (OAB or severe OAB) in both continent and incontinent subjects. Tolterodine ER also reduced urgency urinary incontinence episodes in incontinent subjects. These data show that tolterodine ER is effective and well tolerated in both continent and incontinent subjects with OAB.